PENGARUH INDEKS PLASTISITAS AGREGAT HALUS SUNGAI WAI-TUNSA TERHADAP DAYA DUKUNG LAPIS FONDASI AGREGAT KELAS-B - Frisca Anastasya Leatemia; Selviana Walsen; Hendrie Tahya (Journal Agregate, 2022)
"The Effect of the Plasticity Index of Fine Aggregate of the Wai-Tunsa River on the Carrying Capacity of Class-B Aggregate Base Layers". This thesis is under the guidance of Ms. Selviana Walsen and Mr. Ir. Hendrie Tahya.The purpose of this study is to obtain the effect of the relationship between the value of the Plasticity Index and the CBR value for the final result to be able to determine the carrying capacity of the Class-B Aggregate Base Layer.This study used situ material from the Wai-Tunsa river, Sabuai village, East Seram Regency, and mixed soil which also came from the area around the location where the situ material was taken. The addition of soil to the site was varied by 4%, 8%, 12%, and 16% and then an examination of the Plasticity Index and compaction was carried out to obtain the optimum water content from the optimum water content, a Laboratory CBR examination was carried out to obtain the CBR value.Without the addition of soil, the sand material has a Plasticity Index value = of 4.15% and CBR = of 64.65%. 4% addition of soil obtained IP = 6.88%, CBR = 60.33% , Wopt = 24.15%, and ᵞdmax = 1.40 gr/cm3. 8% variation obtained IP = 7.53%, CBR = 57.95% , Wopt = 24.26%, and ᵞdmax = 1.39 gr/cm3. 12% variation obtained IP = 11.12%, CBR = 56.78% , Wopt = 26.70%, and ᵞdmax = 1.41 gr/cm3. 16% variation obtained IP = 12.08%, CBR = 54.33% , Wopt = 27.76%, and ᵞdmax = 1.40 gr/cm3.It can be concluded that the increase in the value of the Plasticity Index will affect the decrease in the value of the CBR value.Keywords: IP, CBR, Class-B Aggregate.